Traumatic biliary neuroma after orthotopic liver transplantation: a possible cause of "unexplained" anastomotic biliary stricture. Issue 10 (8th August 2016) - Navez, Julie; Golse, Nicolas; Bancel, Brigitte; Rode, Agnès; Ducerf, Christian; Mezoughi, Salim; Mohkam, Kayvan; Mabrut, Jean‐Yves
Abstract: Background: Traumatic biliary neuromas (TBNs) represent a rare cause of biliary stricture (BS) after orthotopic liver transplantation (OLT). Diagnosis is challenging preoperatively and is most often made at pathology after resection. Herein, we report a 20‐year experience of TBN‐related BS. Patients and methods: Medical records of 1030 adult patients undergoing OLT from 1991 to 2014 were reviewed. Patients with histologically proven TBN were identified among those presenting a BS. Results: Over the study period, 52 patients developed an anastomotic BS. Of these, 17 had repeat surgery and specimen examination identified TBN in five instances. All five patients with TBN had a duct‐to‐duct biliary reconstruction during OLT. Median delay from OLT to onset of symptoms was 69 months (range 4–239). Preoperative imaging showed a compressive mass in one patient. Four patients underwent TBN resection combined with hepaticojejunostomy and had an uneventful postoperative course. One patient underwent TBN resection and duct‐to‐duct reconstruction; he died from acute pancreatitis on postoperative day 21. After a median follow‐up of 40.5 months (range 10–54), no recurrent BS occurred. Conclusion: Traumatic biliary neuromas represent a possible diagnosis for unexplained anastomotic BS after OLT. Surgical excision combined with hepaticojejunostomy is effective, allows histological diagnosis, and prevents from recurrence.